Anthropometrical evaluation of Turkish national team before and after altitude training camp - Coskun, F.; Mancevic, D.; Tuncay Özgünen, K.; Özdemir, C.; Sadi Kurdak, S. (Journal of Sports Science & Medicine, 2012)
It is well known that elite, successful swimmers have a specific anthropometric characteristic which is important to determine the athletic performance. The aim of this study was to evaluate the effect of high altitude heavy training program on the anthropometric characteristics of the Turkish national team swimmers. Methods: 17 national team swimmers (11 male and 6 female) aged 19.4 ± 3.1 (mean±SD) were joined to this 3 weeks training program which performed in Pretoria - South Africa at February 2012. Swimmers were trained for 2 sessions per day and each session was divided to dry land and swimming trainings. Somatotype evaluation was measured before and after the training period by utilizing Heath-Carter methodology and body fat percentage was determined as defined by Siri Formula. Pre- and post training statistical evaluation was performed with paired samples t test by the use of SPSSv13.0. Results: Swimmers` pre-training height, body mass and fat percentage was measured as 176.6 ± 10.0 cm, 71.6 ± 10.7 kg and 13.6 ± 5.1 respectively. After 3 weeks of extensive training, body mass and fat percentage was reduced to 71.0 ± 10.8 kg and 10.5 ± 3.9 % respectively (p < 0.05). Training session also affected the somatotype profile of the swimmers. Pre-training ectomorphy (2.6 ± 0.8), endomorphy (2.8 ± 0.8) and mesomorphy (3.8 ± 1.1) was changed significantly after the training camp. Swimmers` post-training ectomorphy, endomorphy and mesomorphy was calculated as 2.7 ± 0.8, 2.5 ± 0.7 and 4.3 ± 1.0 respectively. Swimmers` body muscle mass percentage was increased nearly 1.2 % through out the training period (pre- training 46.6 ± 1.8 to post- training 47.8 ± 2.0). Conclusions: Three weeks intensive training was enough to make a significant change in body composition which presumably may affect their performance. Efficiency of training period may be determined with anthropologic evaluation. Regular calculations of somatotype profile are important to keep elite athletes ready for heavy training and top level competition.